2022
DOI: 10.1097/sap.0000000000003213
|View full text |Cite
|
Sign up to set email alerts
|

Breast Implant–Related Outcomes After Cardiothoracic Surgeries and Electrophysiologic Procedures

Abstract: Background: Outcomes related to preexisting breast implants after cardiothoracic procedures are poorly characterized. This study evaluated complications after minimally invasive cardiac surgery (MICS), median sternotomy (MS), and electrophysiologic procedures (EP) in patients with preexisting breast implants. Methods: A retrospective review of patients with prior breast implants who underwent MICS, MS, or EP from 1994 to 2019 was performed. Demographic, treatment, and outcome characteristics were recorded. χ 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Furthermore, for necessary procedures near breast implants, a consultation with a plastic surgeon may be helpful. This strategy has been shown to reduce the incidence of unexpected complications related to breast implants after cardiac surgery [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, for necessary procedures near breast implants, a consultation with a plastic surgeon may be helpful. This strategy has been shown to reduce the incidence of unexpected complications related to breast implants after cardiac surgery [3].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiothoracic surgery is another known cause of breast implant rupture. In a retrospective study of 78 patients with breast implants who underwent cardiac surgery or pacemaker placement, four patients (5%) developed rupture within 90 days following the surgery [3]. The authors found that patients who underwent median sternotomy were at a higher risk than others.…”
Section: Introductionmentioning
confidence: 99%